Which variable is the strongest adjusted predictor of quality of life in caregivers of patients with dementia?. Issue 1 (17th December 2014) - Abdollahpour, Ibrahim; Nedjat, Saharnaz; Salimi, Yahya; Noroozian, Maryam; Majdzadeh, Reza
Abstract Background The central role of family in caregiving for patients with dementia is now widely acknowledged. However, in playing this role, caregivers may neglect their health and quality of life (QOL). The purposes of present study were to measure caregivers' QOL and to determine its adjusted predictors via multiple regression models. Methods We used sequential sampling to recruit 153 patients and their caregivers from the Iran Alzheimer Association in our cross‐sectional study. A single‐item question with a Likert scale was applied to measure QOL. A multiple linear regression model was used to determine the adjusted predictors of QOL. Results Of the responding caregivers, 22.8% reported their QOL as poor or very poor. Caregiver burden, the main caregiver's age, the Global Deterioration Scale, and the number of caregivers were introduced as adjusted predictors of QOL. Conclusions Caregiver burden was proposed as the strongest adjusted predictor for caregivers' poor QOL. Therefore, it seems that interventions to reduce caregiver burden can be effective in enhancing caregivers' QOL.